Sediment micromorphology and site formation processes during the Middle to Later Stone Ages at the Haua Fteah Cave, Cyrenaica, Libya. Issue 3 (21st October 2017) - Inglis, Robyn H.; French, Charles; Farr, Lucy; Hunt, Chris O.; Jones, Sacha C.; Reynolds, Tim; Barker, Graeme
Abstract: Understanding the timing, conditions, and characteristics of the Middle to Later Stone Age (MSA/LSA) transition in North Africa is critical for debates regarding the evolution and past population dynamics of Homo sapiens, especially their dispersals within, out of, and back into, Africa. As with many cultural transitions during the Palaeolithic, our understanding is based predominantly on archaeological and paleoenvironmental records preserved within a small number of deep cave sediment sequences. To use such sequences as chronological cornerstones we must develop a robust understanding of the formation processes that created them. This paper utilizes geoarchaeological analyses (field observations, sediment micromorphology, bulk sedimentology) to examine site formation processes and stratigraphic integrity during the MSA/LSA at the Haua Fteah cave, Libya, one of North Africa's longest cultural sequences. The depositional processes identified vary in mode and energy, from eolian deposition/reworking to mass colluvial mudflows. These changing processes impact greatly on the interpretation of the paleoenvironmental and archaeological records, not least in identifying potential colluvial sediment deposition and reworking in layers identified as containing the MSA/LSA transition. This study highlights the importance of developing geoarchaeological analyses of cultural sequences to fully unravel the limitations and potential of their contained archaeological and paleoenvironmental records.